Educação ambiental e sensibilização para conservação dos recursos naturais em um assentamento agrícola em Lucena-PB - Córdula, Eduardo Beltrão de Lucena (2015)
The Non-Formal Environmental Education aims at the sensitization of the communities regarding the environmental problems, seeking the restoration of the harmonious relation between humans and the environment. Among the social groups, there are farming communities that, in the rural settlement areas, wage the food production based on the family agriculture. Nonetheless, many communities use in their crops chemical substances to the soil fertilization and pest control. These practices intend to increase the food production in a fewer time. However, these substances may be accumulated on the environment and on the body of the farmers, causing damages, not only environmental, but also to the quality of life of these people. As an alternative to this model, the agro-ecological food production is focused on maintaining productivity in the agricultural areas (with managements based on natural products), on gains in quality of life of the farmers and their families, joining conservation of local natural resources and appreciation of the economy and grown products. This study was conducted with the purpose of analyzing the way and the management of the predominant agricultural production in a rural settlement, as well as the type of conservation and use of local natural resources. The settlement Oiteiro de Miranda is located in the city of Lucena, Paraíba State, with an area of 668 ha and with 82 allotments for 82 families. In this area there are approximately 94.7ha of Legal Reserve of Atlantic Forest, distributed in 16 parts. The research was qualitative, with the use of Ethnographic method, Non-participant observation techniques, interviews with a semi-structured map, and there was a qualitative and descriptive analysis of the data’s content. From the results, actions for sensitization to 50% of the farmers and their family members, who live in the settlement, were planned and carried out, with the aim of making them multipliers. For these actions, there were 13 eco-pedagogical workshops for children and youth and 4 dialogical lectures for adults. The results showed that the predominant management pattern is the traditional one, which uses chemicals in agriculture, and also that there is a resistance to adopt new agro-ecological production models, which is confirmed by the lack of knowledge about this type of management. Part of the population affirmed that they visit and use local natural resources, including those in the areas of Legal Reserve. Socially, it was noticed a disunity among the settlers. The lack of greater propagation of the project and of the actions developed in the settlement, beyond the individual disinterest, made the information processes, the awareness and multiplication of new knowledge among the settlers difficult. This study showed that farmers need a leadership that may unite, stimulate and encourage them to engage them in new changes towards agro-ecological model of agricultural production, to break the paradigm of resistance and making new food production practices. These changes would lead to the conservation of local natural resources and the harmonious coexistence with the environment, to the improvements in the quality of food produced in the settlement and, thus, to the increasing of the quality of their social and environmental life.